dnc-1/dynactin 1 Knockdown Disrupts Transport of Autophagosomes and Induces Motor Neuron Degeneration - Ikenaka, Kensuke (Public Library of Science, 2013)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the progressive loss of motor neurons. We previously showed that the expression of dynactin 1, an axon motor protein regulating retrograde transport, is markedly reduced in spinal motor neurons of sporadic ALS patients, although the mechanisms by which decreased dynactin 1 levels cause neurodegeneration have yet to be elucidated. The accumulation of autophagosomes in degenerated motor neurons is another key pathological feature of sporadic ALS. Since autophagosomes are cargo of dynein/dynactin complexes and play a crucial role in the turnover of several organelles and proteins, we hypothesized that the quantitative loss of dynactin 1 disrupts the transport of autophagosomes and induces the degeneration of motor neuron. In the present study, we generated a Caenorhabditis elegans model in which the expression of DNC-1, the homolog of dynactin 1, is specifically knocked down in motor neurons. This model exhibited severe motor defects together with axonal and neuronal degeneration. We also observed impaired movement and increased number of autophagosomes in the degenerated neurons. Furthermore, the combination of rapamycin, an activator of autophagy, and trichostatin which facilitates axonal transport dramatically ameliorated the motor phenotype and axonal degeneration of this model. Thus, our results suggest that decreased expression of dynactin 1 induces motor neuron degeneration and that the transport of autophagosomes is a novel and substantial therapeutic target for motor neuron degeneration.